Cinco de Mayo : celebrating Hispanic pride - Gnojewski, Carol (Berkeley Heights, NJ : Enslow Publishers, 2002)
Introduces the history, customs, and practices of this holiday commemorating the victory of the Mexican army over the French on May 5, 1862.
6 - 10 years
82311
Keywords: Cinco de Mayo (Mexican holiday) -- History; Mexican Americans -- Social life and customs; Cinco de Mayo, Battle of -- 1862 -- Puebla, Mexico; Cinco de Mayo (Mexican holiday); Holidays; Cinco de Mayo (Puebla, Mexico), Battle of, 1862; Mexico -- Social life and customs